Redesign do livro Brasil Século XX: ao pé da letra da canção popular - Mulinari, Leticia Serro (2014)
This Final Year Research Project consists on the development of a new graphic project for Brasil Século XX - ao pé da letra da canção popular, a book about Brazilian history through the 19th century. Written by Luciana Worms and Wellington Borges Costa, this book presents the peculiarity of approaching Brazilian history through its musical production between this period of time. The present graphic project of this book is built in a very severe structure, similar to bureaucratic documents, and it does not reflect the aspects of the text written by Worms and Costa. This Final Year Research Project considers the subject of the text as the base for the new graphic project proposal. To this end, the present book was analyzed through semantic and syntactic aspects, which revealed opportunities to improve the graphic design and reshape the information. Furthermore, the complete methodological procedures used by the authors of this project are exposed: from a Design Method to a Graphic Design Method, and finally approaching an Editorial Design Method. One of the most important concerns of the authors was the development of a strongly visual graphic language, without compromising the readability and intelligibility, two central aspects when a design project should promote learning. This project, therefore, intends to discuss some fundamental issues, such as the context this publication is inserted in order to consolidate a theoretical basis, allowing a conscious design which will promote a narrower relationship between form and text. This project also intends to discuss some fundamental issues, such as the context this publication is inserted, in order to consolidate a theoretical basis, allowing a conscious design which will promote a narrower relationship between form and text besides improvements on its graphic project.